Defence industries bases (DIB) in six small NATO post-communist countries - Pernica, Bohuslav; Dvorak, Jaroslav; Zsolt, Lazar; Taksás, Balázs; Maskalík, Alex (My University, 2023)
This article investigates the changes in the defense industrial base (DIB) of the small NATO post-communist countries: Czechia, Slovakia, Hungary, Lithuania, Latvia, and Estonia. It considers the historical development of their industries from the Soviet era and the developments caused by the Crimea and Ukraine conflicts. It finds that exports to the markets of the former communist Czechoslovakia continued for Czechia with the DIB owned and controlled by oligarchs—who have been able to leverage this power to influence defense policy. In Slovakia, the DIB is insignificant and mainly under the influence of Czechia. The Hungarian DIB is being redeveloped by the richest members of Hungarian society, through international joint ventures, with the aim of expanding exports. The DIBs of Estonia, Latvia, and Lithuania produce only what is needed by their national armed forces—which seems unlikely to change.
Obranná průmyslová základna (OPZ) šesti malých postkomunistických zemí NATO
Keywords: defence industry; modernisation; Crimea crisis; NATO; post-communism; obranný průmysl; modernizace; okupace Krymu; NATO; post komunismus